Lithium Compounds in Organic Synthesis 2014
DOI: 10.1002/9783527667512.ch8
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur‐Bearing Lithium Compounds in Modern Synthesis

Abstract: Sulfur functions have been widely used for the stabilization of lithium carbanions. Their different oxidation states determine a variety of mechanisms for such stabilization, mainly related with their electronic effects (−I and −M) and associative abilities and also with the relative position of sulfur with respect to the C-Li bond. As additional interest, the sulfur of some of these functions is a stable stereogenic center, and their interactions with prochiral lithium carbanions are able to control the stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 248 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…Chiral α‐heteroatom (O, N, and S)‐substituted organolithium compounds are a versatile class of nucleophiles that are useful in the asymmetric synthesis of chiral alcohols, amines, and thiols . Although the use of secondary and mesomerically stabilized (e.g., benzylic and allylic) tertiary α‐O‐ and α‐S‐substituted organolithium reagents in synthesis is well established,– the use of non‐mesomerically stabilized (i.e., dialkyl‐substituted) tertiary reagents is not. This discontinuity is due to contrasting problematic features governing α‐O‐ and α‐S‐substituted organolithium species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral α‐heteroatom (O, N, and S)‐substituted organolithium compounds are a versatile class of nucleophiles that are useful in the asymmetric synthesis of chiral alcohols, amines, and thiols . Although the use of secondary and mesomerically stabilized (e.g., benzylic and allylic) tertiary α‐O‐ and α‐S‐substituted organolithium reagents in synthesis is well established,– the use of non‐mesomerically stabilized (i.e., dialkyl‐substituted) tertiary reagents is not. This discontinuity is due to contrasting problematic features governing α‐O‐ and α‐S‐substituted organolithium species.…”
Section: Methodsmentioning
confidence: 99%
“…Having demonstrated the broad applicability of tertiary nonstabilized chiral α‐O‐organolithium species, we then embarked on a study of the more challenging sulfur analogues . Pioneering work by Beak had revealed that while the α‐deprotonation of dialkyl‐substituted tertiary thiobenzoates (such as 4 ) was facile at low temperature, they were configurationally unstable even at −98 °C in THF (Scheme A) …”
Section: Methodsmentioning
confidence: 99%
“…Dilithio methandiides 2 are accessible from sulfonyl lithio methanides 1 [9] through α-deprotonation [1,2,4], and from arylsulfonyl dilithio methanides 3 [10,11] though ortho,α-transmetallation [10][11][12][13] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In two different metalation routes, Mulvey et al prepared and characterised (X-ray crystallography/NMR spectroscopy) magnesiated [15] and aluminated tetrahydrothiophene [16] although electrophilic trapping proved challenging. Such metalation approaches [17] build on the pioneering work by Gilman, Wittig, Corey, Seebach and Peterson in the 1940-60s on the α-lithation of dimethylsulfide and thioanisole. [18] Allylic and cyclopropyl-containing acyclic sulfides have also been successfully lithiated and used in synthesis.…”
mentioning
confidence: 99%